Environmental innovation and firm profitability: An analysis with respect to firm size - Janna Axenbeck (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
This paper investigates the effect of environmental innovations on firm profitability with respect to differences between small and medium-sized (SME) and large (LE) enterprises. Using data from the Mannheim Innovation Panel (MIP) 2015, results show that, in general, SME benefit more from environmental innovations than LE. This effect is particularly strong for resource efficiency-improving innovations induced by regulation. These environmental innovations are significantly related to an increase in profits of SME, whilst related to a decrease in profits of LE. A robustness check with data from the MIP 2009, however, does not confirm this result as the effect for LE is insignificant and differences between the two groups cannot be found in this survey wave. A reason why negative effects for LE are observed in the MIP 2015 - but not in the MIP 2009 - might be that most LE had already exploited the potentials of environmental innovations when they were surveyed in the MIP 2015. This is supported by evidence suggesting that size-related differences in the MIP 2015 are driven by a negative relationship between LE's profits and environmental innovations related to externalities that were reduced by innovations in periods before.
Keywords: D22; L25; Q52; Q55; Q58; 330; Firm Behavior; Firm Size; Porter hypothesis; Environmental Technology Adaption; Technological Innovation; Environmental Regulation